Soybean Imports in Indonesia - Rizky Junianto; Hary Sastrya Wanto; Markus Patiung (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Based on its various uses, it produces a high level of consumption of soybeans, but this is not balanced with sufficient domestic production. The increasing population of Indonesia, this further increases the level of soybean consumption. The prospects for soybean development are very good considering that demand continues to increase as the population increases. The growth in soybean demand over the past 34 years is quite high, in line with population growth and the development of the soybean-based food industry. Demand growth is increasingly unbalanced by production growth, so since 1976 Indonesia has always been a net importer of soybeans. The objectives to be achieved in this scientific study are 1) To analyze how much influence soybean production has on soybean imports in Indonesia. Design/methodology/approach: The object of research in this study is Indonesia. The subjects to be studied are soybean imports, to see whether soybean production, soybean consumption, producer soybean prices, the rupiah exchange rate against the United States dollar, soybean exports and soybean import demand in the previous year affected soybean imports using data from 1994 to 2020. The data used in this study is time series data. Findings: The results showed that the Variables of Soybean Production, Soybean Production of Previous Years, Soybean Consumption, Soybean Price consumption of the Previous Year, Soybean Price of the Previous Year, Exchange Rate, soybean exports and soybean exports of the previous year simultaneously influenced the demand for soybean imports in Indonesia. Originality/value: This paper is original Paper type: Research article